Physiotherapy Management in a Case of Post-herpetic Neuralgia Following Herpes Zoster Infection : A Case Report - Karyanto, Muhammad Dhaffa; Suryo Saputra Perdana; Nilam Hamidah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Postherpetic neuralgia (PHN) is a chronic neuropathic pain complication following herpes zoster infection. PHN often leads to persistent pain and facial muscle dysfunction, affecting patients' quality of life. This study aimed to evaluate the physiotherapy management using electrical stimulation and facial exercises in a case of facial PHN. A case report design was used to observe a 36-year-old male patient presenting with facial pain and muscle weakness after herpes zoster infection. The physiotherapy intervention, consisting of electrical stimulation and facial exercises, was conducted over three sessions within two weeks. Assessment tools included NPRS, MMT, and Ugo Fisch Scale. There was a significant reduction in pain from NPRS 5/10 to 0, and improvement in frontal muscle strength from MMT 0 to 3. The Ugo Fisch score increased from 62 to 66, indicating functional improvement of facial muscles, though not yet optimal. Electrical stimulation and facial exercises were effective in reducing pain and improving facial muscle function in a PHN patient. Further research with larger samples is needed to validate these findings.